PENGEMBANGAN PEMBELAJARAN MOTORIK HALUS ANAK TK A MELALUI MEDIA FIGURE GROUND METEAL INSETS DI RA SYIHABUDDIN MALANG - Ari Kusuma Sulyandari; Eka Rosadah; Dwi Wasilah Wati (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study is to help the development of children's early writing with the media figure ground metal insets. This research was conducted at RA Syihabuddin Malang. The small trial of the media was carried out with 6 grade A children and the large trial was carried out involving 35 grade A children. This research method used Barg and Gall's development research with 10 steps, but in this study only 7 steps were used. Media figure ground metal insets is a media owned by Montessori, how to use it is 1) removing the center of the media, 2) drawing according to the shape of the media, 3) shading the image. The data obtained from this research are in the form of safety, fun and easy to do. The results of this study about media security as much as 100%, ease of use of media 93.3% and 100% pleasure level after going through various trials and media evaluations. This learning development deserves to be developed because the percentage is high and is declared good and feasible. Children's early writing ability is also stimulated through the development of ground metal insets figure media.